Mechanism of action and therapeutic use of bempedoic acid in atherosclerosis and metabolic syndrome - Biolo, Gianni; Vinci, Pierandrea; Mangogna, Alessandro; Landolfo, Matteo; Schincariol, Paolo; Fiotti, Nicola; Mearelli, Filippo; Di Girolamo, Filippo Giorgio (Frontiers in Cardiovascular Medicine, 2022)
Bempedoic acid is a new cholesterol-lowering drug, which has recently received US FDA and EMA approval. This drug targets lipid and glucose metabolism as well as inflammation via downregulation of ATP-citrate lyase and upregulation of AMP-activated protein kinase (AMPK). The primary effect is the reduction of cholesterol synthesis in the liver and its administration is generally not associated to unwanted muscle effects. Suppression of hepatic fatty acid synthesis leads to decreased triglycerides and, possibly, improved non-alcoholic fatty liver disease. Bempedoic acid may decrease gluconeogenesis leading to improved insulin sensitivity, glucose metabolism, and metabolic syndrome. The anti-inflammatory action of bempedoic acid is mainly achieved via activation of AMPK pathway in the immune cells, leading to decreased plasma levels of C-reactive protein. Effects of bempedoic acid on atherosclerotic cardiovascular disease, type 2 diabetes and chronic liver disease have been assessed in randomized clinical trials but require further confirmation. Safety clinical trials in phase III indicate that bempedoic acid administration is generally well-tolerated in combination with statins, ezetimibe, or proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors to achieve low-density lipoprotein cholesterol targets. The aim of this narrative review on bempedoic acid is to explore the underlying mechanisms of action and potential clinical targets, present existing evidence from clinical trials, and describe practical management of patients.